THE PERFORMANCE ANALYSIS OF MICRO, SMALL AND MEDIUM ENTERPRISES: THE ROLE OF SELF-EFFICACY, ENTREPRENEURIAL MINDSET AND INNOVATION - Wulandari, Kiki; Parmitasari, Rika Dwi Ayu; Farild, Miftah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The role of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's economy is crucial due to their prevalence in various sectors. Despite their relatively low productivity, MSMEs exhibit resilience during crises. As a result, a large portion of the population relies on MSMEs as their primary source of income. Consequently, fostering self-efficacy, entrepreneurial mindset, and innovation in business processes becomes imperative. This study aims to explore the impact of self-efficacy and entrepreneurial mindset on the performance of MSMEs in Parepare City, with innovation serving as a mediating factor. Employing a quantitative approach, the research involves 140 respondents who are active participants in MSMEs within Parepare City. Utilizing SmartPLS for data analysis, the study investigates the relationship between self-efficacy and entrepreneurial mindset variables and their influence on MSME performance, considering innovation as a mediator. The findings indicate that self-efficacy and entrepreneurial mindset have a positive and significant impact on MSME performance. Additionally, innovation also plays a vital role in enhancing MSME performance. Furthermore, innovation acts as a mediator, effectively channeling the influence of self-efficacy and entrepreneurial mindset on MSME performance